Tinjauan Literatur Terhadap Perkembangan Kurikulum Pendidikan Matematika di Indonesia Dari Masa Ke Masa - Haq. MY, Annisa Husnul; Kusumah, Yaya S.; Dahlan, Jarnawi A. (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
ABSTRACT: In mathematics subjects, reviewing the development of the curriculum in Indonesia is a step in adapting to global dynamics in the aspect of education, student needs, and demands from the development of the times. Some examples of challenges faced by the development of the education curriculum in Indonesia from time to time are the lack of teacher readiness in adopting new approaches, the gap between implementation in the field and the concept, and inconsistencies between curricula. The purpose of the study is to analyze the development of the mathematics education curriculum in Indonesia from time to time. The writing of this journal uses a qualitative research type. The findings of the study are the development of the mathematics education curriculum in Indonesia from time to time starting from the 1994 Curriculum, KBK (2004), KTSP (2006), 2013 Curriculum, and the Independent Curriculum. Reviewed from the assessment, education starts from a written exam to a formative and holistic assessment. Furthermore, reviewed from student involvement in the 1994 curriculum, passive student involvement was found until the independent curriculum experienced an increase in student involvement to become very active personally. In terms of the role of teachers, there has also been an increase in the development of the curriculum, namely starting from the dominant method of lectures, facilitators, and collaborating facilitators. Furthermore, the flexibility of the curriculum has also increased from the